ANÁLISIS DE REQUERIMIENTOS PARA EL DESARROLLO DE UN SOFTWARE DE GESTIÓN DE DOCUMENTOS EN EL CENTRO MÉDICO SANTA ROSA DE BABAHOYO - Ortega Galarza, Belinda Erminia (2018)
This case study arises from the need to identify and analyze the requirements of the document management software development at Santa Rosa Medical Center in the city of Babahoyo. In the Santa Rosa medical center, information is obtained on all the patient's data, which go to the place for medical attention, because the data and documents are stored in the server of the medical center. These are handled in folders to be stored on the server frequently, this would be a very unusual way so the information is lost and often the documentation stored on the server of the medical center can be extracted, at the moment of sending the information it arrives incomplete and generates problems in the digitization area. A comparative study was made of the different types of requirements that are identified in the methodologies for software development. It should be possible to implement each requirement according to the capabilities and limitations of the system and the environment that surrounds it. The technical restrictions are related to the limitations of the platforms and the hardware and software architectures used within the study. This case study is carried out to inform about the problems that exist in the Santa Rosa Medical Center of the city of Babahoyo in terms of the analysis of the requirement for the development of the software with the documentation management. The study is mainly done as a process or program, through which it seeks to normalize and rationalize the life cycle of documents, from planning to their elimination or permanent conservation.